If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5u + 6v + -3(3u + -2v) = 0 5u + 6v + (3u * -3 + -2v * -3) = 0 5u + 6v + (-9u + 6v) = 0 Reorder the terms: 5u + -9u + 6v + 6v = 0 Combine like terms: 5u + -9u = -4u -4u + 6v + 6v = 0 Combine like terms: 6v + 6v = 12v -4u + 12v = 0 Solving -4u + 12v = 0 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-12v' to each side of the equation. -4u + 12v + -12v = 0 + -12v Combine like terms: 12v + -12v = 0 -4u + 0 = 0 + -12v -4u = 0 + -12v Remove the zero: -4u = -12v Divide each side by '-4'. u = 3v Simplifying u = 3v
| 2n-4m=8 | | 12s^2-13st-4t^2= | | 15x-10=-9x+12 | | 10x+1=2x+5 | | 41-8x=-6x-23, | | 3(3x+4)-2-5-7x=20 | | -7q+8-6+5q=8 | | 3x+16=12x-74 | | -r+7r-3+5r=93 | | w=mt+b | | =2(3s-8)+7 | | -(4x-4)-(-2x-6)+3=-3(x-1)-(6x+2)+3 | | 2b-10b-15+5=8b-40-4b-6 | | 10x^4-21x^2+9= | | 6a+3a=18 | | 3x+14+2x+1=180 | | 11a-4a-18=2a+a+10 | | 9x-5x-x=9 | | 9x-5x-x=19 | | 4x^4+8x^3+3x^2= | | 7c-4c+5-8+c=29 | | 7=x^2+x+8 | | x(x^2-2)=0 | | 0=-8(2t^2-t-45) | | 8m-4m-6-3+5m=63 | | x(x^2-2)-4=0 | | 8q-q+7-4-3q=47 | | H=-16t^2+108t+520 | | 4f+6f=8 | | 4n+n=15 | | 4x+x+10=90 | | 0=3y-10+4y |